An autonomous tumor-targeted nanoprodrug for reactive oxygen species-activatable dual-cytochrome c/doxorubicin antitumor therapy. Issue 24 (8th June 2018) - Pei, Yuxia; Li, Menghuan; Hou, Yanhua; Hu, Yan; Chu, Guangyu; Dai, Liangliang; Li, Ke; Xing, Yuxin; Tao, Bailong; Yu, Yonglin; Xue, Chencheng; He, Ye; et al.
Abstract : Cytochrome c/doxorubicin dual therapy triggered by the high level of reactive oxygen species in tumor tissues. Abstract : The precise tumor cell-specific delivery of therapeutic proteins and the elimination of side effects associated with routine chemotherapeutic agents are two current critical considerations for tumor therapy. In this study, we report a reactive oxygen species (ROS)-activated yolk–shell nanoplatform for the tumor-specific co-delivery of cytochrome c (Cyt c) prodrug and doxorubicin, in which the bioactivity of Cyt c could be restored by the intracellular ROS-trigger and readily initiate the sequential doxorubicin release. The DOX-loaded lactobionic acid-modified yolk–shell mesoporous silica nanoparticles were first encapsulated with 4-nitrophenyl 4-(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)benzyl carbonate (NBC)-modified Cyt c via boronic ester linkages, and functionalized again with lactobionic acid to further shield Cyt c and confer the selective tumor targeting against liver cancer cells. The key feature in this design is that by taking advantage of the boronic ester linkage, the cytotoxicity of Cyt c capped on the nanoparticle could be temporarily deactivated during blood transportation and rapidly restored upon exposure to the ROS-rich microenvironment within liver cancer cells, thereby simultaneously achieving the protein therapy and stimuli-responsive doxorubicin release. This study presents a novel strategy for the development of tumor-sensitive co-delivery nanoplatforms.